Produção de biodiesel via extração e reação integradas a partir do farelo de arroz e solventes verdes pressurizados - Hollas, Suelly Ribeiro (2024)
This research evaluated the production of fatty acid methyl esters (FAME) and fatty acid ethyl esters (FAEE) from rice bran (RB) using an integrated extraction and reaction process with pressurized ethanol and dimethyl carbonate (DMC) as solvents. Initially, Pressurized Liquid Extraction (PLE) was evaluated in semi-continuous mode (120 and 150 °C, with a solvent/feed ratio of 96 and 192 mL g-1 , equivalent to flow rates of 4 and 8 mL min-1 ) using ethanol, DMC and their 1:1 mixture. Based on the best PLE conditions, the integrated system for oil extraction and subsequent reaction of rice bran oil (RBO) was evaluated in continuous mode and under sub- and supercritical conditions (250 °C and 300 °C). Soxhlet extraction was performed for comparison in terms of oil yield and quality. The RB used in the tests, with a granulometry of 42 mesh, presented moisture, ash and oil contents of 11.83 ± 0.76 m.%, 9.84 ± 0.04 m.% and 20.08 ± 0.99 m.%, respectively. Soxhlet extraction resulted in oil yields of 15.79 ± 0.31 m.% (ethanol), 21.42 ± 0.79 m.% (DMC), and 27.82 ± 0.51 m.% (DMC:Ethanol mixture). In PLE, the conditions of 120 °C and 192 mL g-1 provided the highest yields and best oil quality, in terms of acylglycerols, for both ethanol (20.68 ± 0.37 m.%; 94.45 ± 2.33 m.%) and DMC (21.69 ± 0.47 m.%; 91.30 ± 2.70 m.%), in 60 min of processing. Furthermore, PLE generated a product with lower water content, averaging 0.05 m.%. In the integrated extraction and reaction process, DMC achieved a maximum FAME yield of 96.97 ± 5.73 m.% in 20 min at 250 °C, with an ester content of 88.54 ± 5.23 m.%. For ethanol, the highest ester content and yield were 75.57 ± 1.65 m.% and 80.00 ± 1.74 m.%, respectively, at 300 °C and 10 min of experiment. The results indicate that integrating the extraction and reaction steps into a single continuous system represents an efficient and sustainable alternative for biodiesel production, using a low-cost raw material and eliminating the need for prior oil purification. This study reinforces the potential of RB for biofuels production, contributing to the development of innovative and environmentally sustainable technologies.